#TITLE_ALTERNATIVE# - AYU PURNAMASARI (NIM 12905013), IDA
Coral is a main organism on a coral reefs, which produces the calcium carbonate (CaCO3) and formed the reef basic structure (Nybakken, 1992). Measurements of luminescence for coral growth data processing, which from Bidadari, Air and Jukung Island, is used by CoralXDS (Helmle, 2002). Based on the data, linear extension banding coral could be identified by the bright/darkness level, which represents the low/high density. Linear extension and age of the three corals are obtained by the pair of bright/darkness level. Besides, the chronology also could be determined. Based on the data processing, constructed an age model for the three cores: Bidadari 49 years (1957-2005), Air 83 years (1925-2007) and Jukung 123 years (1883-2005). The linear extension rates are: Bidadari 1.68 cm/year, Air 1.29 cm/year and Jukung 1.41 cm/year. On the 1957-2005 period, Bidadari's coral (inshore) is more affected by population and their activities than offshore coral. Sea surface temperature and precipitation have less influence for the three cores in the same period. El Nino and La Nina event give different influences either on linear extension and sea surface temperature in Indonesian waters.